OCCASIONS OF USER DATA COLLECTING IN ONLINE SOCIAL NETWORK SERVICES:TWITTER'S TERMS OF SERVICE AND PRIVACY POLICY ANALYSIS - Conceição, Dejan Martins; Gomes, Amanda Garcia [UNESP]; da Silva, Larissa Lima; de Assis Rodrigues, Fernando; Sant'Ana, Ricardo Cesar Gonçalves [UNESP] (My University, 2024)
Introduction: The collection of data carried out by Online Social Network Services raises concerns regarding the privacy of their users, as it allows the online behavior and personal data of these individuals to be quantified and explored as economic assets that support the companies that own and operates the Online Social Network Services. Objective: Therefore, this article aims to identify the occasions of data collection by the Twitter Online Social Network Service based on the analysis of the Terms of Service and the Privacy Policy. Methodology: This research is descriptive and exploratory with a qualitative nature that uses the content analysis method applied to Twitter's Terms of Service and Privacy Policy. Results: We identified twenty collection occasions, divided into three purposes: processing Twitter services, providing services, and sharing data with external agents via the Application Programming Interface. Conclusions: There is opacity regarding the collection occasions and data sets collected by Twitter, given the dispersed information about this process in the legal documentation of this Online Social Network Service. Furthermore, it was possible to detect several possible combinations for data collection to occur, even if, at some point, the item is previously vetoed in the Terms of Service, which implies potential risks to the privacy of Twitter users.
OCASIÕES DE COLETA DE DADOS EM SERVIÇOS DE REDES SOCIAIS ONLINE: Análise dos Termos de Serviço e da Política de Privacidade do Twitter
Keywords: Data collecting; Online Social Network Services; Privacy; Terms of Service